Sistem Informasi Pengelolaan Sampah Kabupaten Bantul Berbasis Website Menggunakan Model Modified Waterfall: Bantul Regency Waste Management Information System Based on Website Using Modified Waterfall Model - Yulianto, Dinan; Febrianto, Aldi (Pandawan Incorporation, Alphabet Incubator Universitas Raharja, 2025)
Waste management that is carried out conventionally or not integrated and coordinated between the government, the community, and the private sector creates new, increasingly complex problems. The Bantul Regency Government has established a Waste Management program based on Village-Owned Enterprises (the BumKal), which involves the synergy of all stakeholders. This research aims to develop and evaluate a web to optimize data management and monitoring: waste shodaqoh; waste bank; waste management place; and other BumKal programs. The process of developing a web applies the Software Development Life Cycle principles with the modified Waterfall model, which consists of stages: requirements definition; system and software design; implementation and unit testing; integration and system testing; as well as operation and maintenance. This research succeeded in developing a web to optimize BumKal program services. Efforts to evaluate web pages from unit level to overall functional integration through black box tests succeeded in achieving 100% conformity to functional aspects. The final stage of this research is to submit a web to the Environmental Service in Bantul Regency to optimize the BumKal program.